2016
DOI: 10.1039/c6ob00894a
|View full text |Cite
|
Sign up to set email alerts
|

A six-membered-ring incorporated Si-rhodamine for imaging of copper(ii) in lysosomes

Abstract: The regulation of copper homeostasis in lysosomes of living cells is closely related to various physiological and pathological processes. Thus, it is of urgent need to develop a fluorescent probe for selectively and sensitively monitoring the location and concentration of lysosomal Cu(2+). Herein, a six-membered ring, thiosemicarbazide, was incorporated into a Si-rhodamine (SiR) scaffold for the first time, affording a SiR-based fluorescent probe SiRB-Cu. Through the effective Cu(2+)-triggered ring-opening pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 43 publications
1
16
1
1
Order By: Relevance
“…reported a Rhodamine B analogue of Si‐rhodamine, which possesses bathochromic shifts in the absorption and fluorescence maxima compared to the tetramethylrhodamine analogue, SiR650, (Figure ; compound 20 , Table ) and they also established an efficient synthetic scheme for this scaffold . This fluorophore was derivatized to afford fluorescent probes for nitric oxide, Cu 2+ and Hg 2+ , based on the spirocyclization mechanism . Lavis et al.…”
Section: Introductionmentioning
confidence: 99%
“…reported a Rhodamine B analogue of Si‐rhodamine, which possesses bathochromic shifts in the absorption and fluorescence maxima compared to the tetramethylrhodamine analogue, SiR650, (Figure ; compound 20 , Table ) and they also established an efficient synthetic scheme for this scaffold . This fluorophore was derivatized to afford fluorescent probes for nitric oxide, Cu 2+ and Hg 2+ , based on the spirocyclization mechanism . Lavis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Current molecular design in NIR probes uses BODIPY, 5,6,7 benzofuran, 8 rhodamine, 9 and cyanine 10 as fluorophores, which typically exhibit small Stoke’s shift. In addition, most NIR lysosome probes are including an amine group in the probe design.…”
mentioning
confidence: 99%
“…10 Furthermore, high levels of A highly selective fluorescent probe for the sensing of Cu 2+ based on the hydrolysis of a quinoline-2-carboxylate and its application in cell imaging copper ions accumulating in lysosomes in the higher oxidative state (Cu 2+ form) cause serious damage to living cells. [11][12][13][14] Therefore, it is desirable to design new methods and tools for the sensing of intracellular copper ions.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Scheme 1, probe 1 was obtained in high yield by the esterification of compound 2 with quinoline-2-carboxylic acid. The product was fully characterized by 1 H NMR, 13 C NMR, and high-resolution mass spectrometry (HRMS) (see Figures S1-S5, Supporting Information). Further studies revealed that probe 1 exhibits high selectivity and sensitivity for Cu 2 over other cations and anions with a low detection limit of 0.2 μM.…”
Section: Introductionmentioning
confidence: 99%